Evaluation of statistical extrapolation methods for ship dynamic stability assessment - Κακλαμάνης, Ελευθέριος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ναυπηγών Μηχανολόγων Μηχανικών. Τομέας Μελέτης Πλοίου και Θαλάσσιων Μεταφορών, 2018)
This study presents a thorough evaluation of statistical extrapolation methods for the prediction of extreme motions of a ship rolling in realistic beam seas. We will use several extrapolation techniques to predict the tail distribution of roll response with datasets obtained from Monte Carlo Simulations.